2018
DOI: 10.1016/j.ijso.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Emergency laparotomy outcomes before and after the introduction of an acute surgical unit

Abstract: Introduction: Emergency laparotomy is associated with significant morbidity and mortality. This study compared emergency laparotomy outcomes in a traditional service to those after the introduction of an Acute Surgical Unit (ASU). Methods: A retrospective cohort study was performed by reviewing the medical records of all individuals that had an emergency laparotomy in twelve-month periods before and after the introduction of an ASU. Outcomes included ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Urgent laparotomy is associated with significant increased risk of mortality and is reported to be approximately 15% [13,14]. However, this number might vary and depends on the indications, specific patient characteristics, and health system factors [13,22]. Acute peritonitis remains an important cause of morbidity and mortality in emergency abdominal surgery [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Urgent laparotomy is associated with significant increased risk of mortality and is reported to be approximately 15% [13,14]. However, this number might vary and depends on the indications, specific patient characteristics, and health system factors [13,22]. Acute peritonitis remains an important cause of morbidity and mortality in emergency abdominal surgery [23].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality in intra-abdominal sepsis ranges from 28% to 47% [22,24,25]. Sepsis is a life-threatening complication [13,21] of peritonitis. Our study confirmed a worldwide problem of undiagnosed sepsis, which is common in all departments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the included articles reported on-site night-time attending coverage of an ASU. Six of the ASU's described were a separate (sub)unit from other surgical services [36][37][38][41][42][43]. Six articles described coverage of the ED by the ASU team or resident during working hours [37,38,43,46,48,49] [38,[47][48][49].…”
Section: Australasiamentioning
confidence: 99%